Evaluasi Gambar Desain Rumah Susun Pemkot Semarang Berdasarkan Pedoman Teknis Pembangunan Rumah Susun Di Indonesia - Firmansyah, M Alfian (Universitas Negeri Surabaya, 2023)
The construction of flats is a solution to address housing needs in big cities. The construction of flats still needs to pay more attention to regulatory provisions in Indonesia and the place where they are built. According to the survey results, Semarang City Government Flats still have some discrepancies in their designs with regulations in Indonesia which are found in terms of space and building accessibility. The research objective is to evaluate and redesign the Semarang City Government Flats and visualize them in 3D to help understand the research. The method used in this research is a quantitative method requiring primary and secondary data. The evaluation is in the form of assessing the design drawings of the Semarang City Government Flats to determine which aspects are appropriate and which are not under regulations in Indonesia. Then it will be redesigned under regulations in Indonesia on aspects that are not suitable and have yet to be fulfilled in the initial design. The concept of redesigning Flats focuses on fulfilling its functional aspects in the form of primary, secondary, and tertiary functions. After the redesign, a 3D visualization will be done on the redesigned Semarang City Government Flats building. The results showed that the building design of the Semarang City Government Flats obtained a percentage value of the conformity of the design drawings with regulations in Indonesia reaching 70.15% (Decent). The redesign was carried out by improving the room's dimensions that needed to be corrected and adding rooms that were not included in the initial design for aspects of the room. As for the accessibility aspect, there are dimension improvements in several building items, such as doors and stair railings, that are not yet under regulations in Indonesia.